L’impatto della depressione perinatale e il ruolo dell’allattamento al seno nello sviluppo del bambino - Di Cesare, Diletta (Il sogno della farfalla, 2019)
This article focuses on perinatal depression. The author examines the results of recent scientific studies analysing the impact of mothers’ perinatal depression on child’s growth and cognitive, social, language skills development. The author discusses the research she carried out at the King’s College University of London looking at data extrapolated from the widest Pram-D study. The objective of the research is to study the negative impact of the mother’s depression on the child development at 1 year of age. This study particularly focuses on the role played by breastfeeding, starting from the assumption that depressed mothers are less likely to breastfeed their children.